Chemopreventive effect of spirulina microalgae on an animal model of glioblastoma via down‐regulation of PI3K/AKT/mTOR and up‐regulation of miR‐34a/miR‐125B expression. (4th October 2021) - Arab, Samaneh; Ghasemi, Sahar; Ghanbari, Ali; Bahraminasab, Marjan; Satari, Atefeh; Mousavi, Mahboubeh; Dehcheshme, Hesamodin Ghasemi; Asgharzade, Samira
Abstract : Recent studies suggest that Spirulina may have great therapeutic benefits due to its antioxidant and anti‐inflammatory properties. The primary objective of this study was to evaluate the chemopreventive properties of the Spirulina microalgae (Spi) on the regression and survival of tumor, histopathological features of glioblastoma, and detection of the molecular mechanism of Spi. Tumor viability versus Spi was determined using the MTT assay. In vivo antitumor activity of Spi was studied using the glioblastoma model. After tumor induction, the animals were euthanized, and their brains were removed. Histological evaluation was performed for tumor size and manifestation. The mechanisms of the anticancer effects of Spi were investigated by evaluating the microRNAs and their targets. The results demonstrated that Spi inhibited C6 and U87 cell proliferation and induced cell death. Histopathologic results showed that the administration of Spi could delay the development of tumors and prolonged the survival of tumor‐bearing animals. Furthermore, Spi significantly upregulated miR‐34a and miR‐125b that have a key role in the progression of PI3K/AKT/mTOR pathway. This is the first in vivo report on the chemo‐preventive effect of Spi against glioblastoma, suggesting its potential use in the chemoprevention of this cancer and the antiglioma molecular mechanism of Spi.